Implementing a multichain framework using hyperledger for supply chain transparency in a dynamic partnership: A feasibility study. (January 2023) - Chou, Chi-Chun; Richard Hwang, Nen-Chen; Li, Chang-Wei; Wang, Tawei; Wang, Yen-Yao
Highlights: A multichain, permissioned blockchain framework for supply chain transparency. Resolves information sharing dilemma in a dynamic supply chain setting. Implements access control and addresses data aggregation issues in proof-of-concept. Abstract: As an emerging technology, blockchain is appealing because it ensures authenticity and legitimacy of business activities, improves traceability of products, and enhances supply chain transparency (SCT), thus strengthening trust and confidence among partners. Although academicians and practitioners agree that information sharing is imperative to improve SCT, it is unclear whether and how organizations can take advantage of blockchain technology to manage information sharing when collaborating with partners and competitors in a dynamic supply chain while maintaining privacy and confidentiality. In this study, we attempt to address this issue by building multiple assets and chains with multiple processes, facilitating data aggregation, and maintaining information confidentiality. To achieve these objectives, this study proposes a multi-asset, multichain framework and builds a permissioned blockchain network using Hyperledger Fabric. By constructing "channels" under the proposed framework, this study demonstrates that firms can share information privately and confidentially with partners and competitors in a supply chain and simultaneously improve SCT. Overall, the results obtained from the proof-of-concept analysis suggest that the proposed framework outperforms the public blockchain in terms of information sharing and SCT perspectives.